Psychometric Properties of Three Simplified Chinese Online-Related Addictive Behavior Instruments Among Mainland Chinese Primary School Students - Chen, I-Hua; Ahorsu, Daniel Kwasi; Pakpour, Amir H.; Griffiths, Mark D.; Lin, Chung-Ying; Chen, Chao-Ying (Frontiers in Psychiatry, 2020)
Background/Objective: There are inadequate instruments for assessing specific internet-related addictions among mainland Chinese who are primary school students. Therefore, this study aimed to validate the psychometric properties of three simplified Chinese online-related addictive behavior instruments among mainland Chinese primary school students. Method: Fourth to sixth graders (n = 1108; 48.3% males) completed the Internet Gaming Disorder Scales- Short Form (IGDS-SF9), Bergen Social Media Addiction Scale (BSMAS), and Smartphone Application-Based Addiction Scale (SABAS) in a classroom. The factorial structures and the unidimensionality of the three scales were examined using Confirmatory factor analyses (CFAs). Measurement invariance of the three scales was examined using multigroup confirmatory factor analyses (MGCFA) across gender. Results: The findings revealed that the three scales (Cronbach’s α = 0.73 to 0.84) had unidimensional structure as supported by satisfactory fit indices (comparative fit index = 0.98 to 1.00). The MGCFA findings indicated that the unidimensional structures of the three scales were invariant across gender. Conclusions: The findings indicate that the three simplified Chinese scales (IGDS-SF9, BSMAS, and SABAS) are valid instruments for assessing online-related addictive behaviors among mainland Chinese primary school students irrespective of their gender.